An ecological approach to normativity. (February 2016) - Lo Presti, Patrizio
It is argued that normativity is an embodied and situated skill that resists explanation in terms of rule-following. Norms are dynamic and negotiable, and are understood in practice by engaging with others. Rules are a subclass of norms and have pragmatic functions, e.g., to impose norms and elucidate implicit normativity. The propositional articulation of norms is secondary to normativity. Norms can be explained within the framework of ecological psychology as a particular kind of affordance that enables actions to be directly understood as correct. This view entails that the niche of human beings is inherently normative. Finally, the ecological account of normativity is used to elucidate the notion of rule-following.